Fiqh Fardhu Kifayah for the City of Covid-19 According to the Fatwa of MUI and Permenkes Number 413 (Maqashid Syariah Analysis) - Muhammad Syukri Albani Nasution; Wulan Dayu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Maqashid al-syari'ah is an important discussion in Islamic Law that does not escape the attention of scholars and experts in Islamic law. Some of the scholars put it in the discussion of ushul fiqh, and other scholars discussed it as an adult and extensive material in the philosophy of Islamic Law. If you examine all the commands and prohibitions of Allah in the Qur'an, as well as the commands and prohibitions of the Prophet SAW in the sunnah formulated in fiqh, it will be seen that all of them have a specific purpose and nothing is in vain. The provisions that are currently used in the momentum of rules or regulations in implementing worship during the ongoing COVID-19 pandemic. Likewise with the scholars, including the MUI, which issued fatwa Number 18 of 2020 concerning Guidelines for the Management of the Body (tajhiz al-jana'iz) of Muslims infected with Covid-19 determined that: Muslims who died because of the COVID- 19 outbreak in the view of syara 'include the category of martyrdom in the hereafter and the rights of the corpse must be fulfilled, namely to be bathed, dipped in, and buried, the safety of which is mandatory for the safety of the officer under the provisions of the medical protocol. Regarding this condition, the author tries to find answers to these questions by using qualitative research methods with related results and sources, namely the fatwas issued by the Indonesian Ulama Council as the main research instrument. In the case that is explicit or explicit by the text of the Koran, the benefits can be traced in both sources. If an explicit and explicit maslahat is in the text, then that benefit is used as a benchmark for legal determination, and scholars are commonly referred to by the term al-mashlahah al-mu'tabarat.